Association of branched-chain amino acid intake trajectory in adulthood with the risk of type 2 diabetes and its related risk factors. Issue 1 (5th January 2022) - Wang, Weiqi; Han, Tianshu; Hou, Wanying; Ren, Xiyun; Duan, Wei; Liu, Zhipeng; Sun, Changhao
Abstract : Supplemental Digital Content is available in the text